Congresses of Mining Industrialists of the South of Russia and the Kingdom of Poland as a form of Representing Entrepreneur’s Interests (End of the 19th – Beginning of the 20th Century) - Shandra, Iryna; Kravchenko, Olena (Studia Historiae Oeconomicae, 2020)
The article analyzes the process of creating and functioning of two representative organizations of entrepreneurs – the Congress of Mining Industrialists of the South of Russia (1874, Kharkiv) and the Congress of Mining Industrialists of the Kingdom of Poland (1882, Warsaw). Both institutions were a form of activity of the regional economic elites and represented their socio-economic interests. After a comparative analysis of associations of mining industrialists in Ukrainian and Polish territories, the article highlights common features, their structure, forms of activity and representative powers. Based on the research, it was found that, despite strict government control, they played an important role in defending local interests and developing the industry they represent, and the fruitful cooperation of the Miners’ Congresses of the South of Russia and the Kingdom of Poland allowed for the implementation of the agreed and, above all, effective pressure on the state authorities of the Russian Empire.